Development of Architectural and Landscape Space Collective Purpose in Low-Rise Buildings - Bakhodirovna, Yunusova Kamola (Researchparks Publishing, 2023)
In the article it is considered the development of public welfare’s landscape of high-rise buildings in the historical part of Samarkand city and its planning, its decorative designing.